Epidemiology of hepatitis B and C among risk groups in Czechia - Iva Bendlova; Vojtech Simka; Ekaterina Ryzhova; Tereza Schovankova; Ondrej Holy (BMC Public Health)
Abstract Hepatitis B (VHB) and C (VHC) are significant global public health issues, particularly for certain risk groups. In the Czech Republic, individuals who inject drugs (IDUs), incarcerated people, and those with high-risk sexual behaviours are especially susceptible. This research investigates the epidemiology, risk factors, and effects of both diseases on these groups. It analyzes the incidence of VHB and VHC in Czechia over the last twenty years in the post-vaccine era, compares their occurrence, and identifies factors influencing their rates. A total of 28,160 VHB and VHC cases reported in the Czech Republic from 2000 to 2021 were analyzed, categorized into acute and chronic forms. Specifically, there were 8,762 cases of VHB and 19,398 cases of VHC. The research employed quantitative methods and descriptive data analysis. A spatial visualization of disease occurrence per 100,000 inhabitants in Czech districts was conducted for the years 2000, 2010, and 2020 to compare disease development and the risk group of IDUs across districts. For VHB, transmission primarily occurs through intravenous drug use or risky sexual behaviour, with IDUs, men who have sex with men, and promiscuous individuals being the most at-risk groups. For VHC, sexual transmission is less common, with IDUs being the most at-risk group. Many VHC cases have been recorded in prisons, often due to shared razors or amateur tattooing and piercing. This discovery underscores the necessity for focused interventions and thorough strategies to address both diseases in high-risk communities.